2003
DOI: 10.1104/pp.103.030379
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Hormones Act Sequentially to Mediate a Susceptible Tomato Pathogen Defense Response

Abstract: Phytohormones regulate plant responses to a wide range of biotic and abiotic stresses. How a limited number of hormones differentially mediate individual stress responses is not understood. We have used one such response, the compatible interaction of tomato (Lycopersicon esculentum) and Xanthomonas campestris pv vesicatoria (Xcv), to examine the interactions of jasmonic acid (JA), ethylene, and salicylic acid (SA). The role of JA was assessed using an antisense allene oxide cyclase transgenic line and the def… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
104
2
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(120 citation statements)
references
References 46 publications
10
104
2
2
Order By: Relevance
“…In these experiments, the transcription of TLC1 was activated in response to wounding and Onozuka R10 cellulase in a similar way to that described for other active retrotransposons (Pouteau et al, 1991;Mhiri et al, 1997;Takeda et al, 1998Takeda et al, , 1999. These results correlate with the induction of TLC1 in response to ethylene, methyl jasmonate, and salicylic acid, which were described to be involved in signal transduction pathways associated to the abovementioned stress conditions (O'Donnell et al, 1996(O'Donnell et al, , 2003.…”
Section: Transcriptional Induction Of Tlc1 In Response To Stress Condsupporting
confidence: 75%
See 1 more Smart Citation
“…In these experiments, the transcription of TLC1 was activated in response to wounding and Onozuka R10 cellulase in a similar way to that described for other active retrotransposons (Pouteau et al, 1991;Mhiri et al, 1997;Takeda et al, 1998Takeda et al, , 1999. These results correlate with the induction of TLC1 in response to ethylene, methyl jasmonate, and salicylic acid, which were described to be involved in signal transduction pathways associated to the abovementioned stress conditions (O'Donnell et al, 1996(O'Donnell et al, , 2003.…”
Section: Transcriptional Induction Of Tlc1 In Response To Stress Condsupporting
confidence: 75%
“…Several studies have revealed the existence of ethylene-dependent signaling pathways activated in response to pathogen attack (Dong, 1998;Guo et al, 2000;Díaz et al, 2002), wounding (O'Donnell et al, 1996;Watanabe et al, 2001), UV irradiation, and ozone exposure (Wang et al, 2002). In such cases, ethylene acts in a coordinated way with other signaling molecules such as salicylic acid and jasmonic acid, suggesting the existence of a complex network of regulatory pathways (Dong, 1998;Wang et al, 2002;O'Donnell et al, 2003;Guo and Ecker, 2004). Consequently, the residual GUS activity detected in protoplasts transformed with the single or double TRS mutant constructs (Fig.…”
Section: The U3 Domain Of Tlc11 5# Ltr Includes Cis-acting Eresmentioning
confidence: 99%
“…It has been recently shown, by monitoring bacterial growth in tomato mutants defective in jasmonic acid or ethylene signaling, that these two hormones do not affect resistance to Xcv, but they do affect the extent of cell death (39). Interestingly, activation in tobacco of MAP kinase cascades, which include the NtMEK2 MAPKK and the SIPK and WIPK MAP kinases, has been reported to cause an increase of ethylene levels (18).…”
Section: Discussionmentioning
confidence: 99%
“…Buchanan-Wollaston et al, 2005). Considering that Xcv infection induces SA levels (O'Donnell et al, 2003;Block et al, 2005) and XopD action delays leaf chlorosis and necrosis ( Figure 1B), we hypothesized that XopD action might be affecting SA levels in the diseased tissue. To test this, we estimated the SA pool (i.e., free SA plus existing methyl salicylate) in susceptible VF36 leaves inoculated with Xcv over the course of 10 d ( Figure 3A).…”
Section: Xopd Reduces Sa Levels In Leaves Infected With XCVmentioning
confidence: 99%